Implementation and Evaluation of a Pediatric Pain Education Program for Healthcare Providers in Ghana: A Multidisciplinary Approach - Kusi Amponsah, Abigail; Hammond, Charles Kumi; Bam, Victoria; Gyamfi, Douglas; Armah, Jerry; Wilson, Dorothy; Annobil, Faithful; Ba‐Eebu Badengo, Daniel; Kyei Dompim, Joana; Axelin, Anna; Nawagi, Faith; Mukherjee, Snighda (Wiley, 2026)
Pediatric pain remains one of the inadequately managed conditions in clinical practice, especially in low-resource settings, due in part to limited training across health professions. Addressing this gap requires a coordinated, multidisciplinary approach to improve pain assessment and management in children. This study aimed to implement and evaluate a multidisciplinary pediatric pain education program to enhance healthcare professionals' (HCPs) knowledge, attitudes, and self-efficacy. A one-group pretest-posttest quasi-experimental design was conducted among HCPs from diverse professional backgrounds at the Kwame Nkrumah University of Science and Technology (KNUST) Hospital. A 45–60-min educational session on pediatric pain assessment and management was delivered to participants. Knowledge and attitudes were assessed using the Pediatric Healthcare Providers' Knowledge and Attitudes Survey Regarding Pain (PHPKASRP), and self-efficacy was assessed using a validated six-item tool. Program acceptability was evaluated using a structured training evaluation form. Quantitative data were analyzed using the Wilcoxon signed-rank test. Open-ended responses were analyzed using content analysis guided by Kirkpatrick's evaluation model. A multidisciplinary group including 10 nurses, 14 pharmacists, and 11 physicians participated in the study. Participants demonstrated statistically significant improvements in knowledge and attitude scores (z = −5.118, p < 0.001), as well as self-efficacy scores (z = −4.79, p < 0.001), following the educational program. The standard score for knowledge and attitude improved from 49.54 to 68.63, and self-efficacy scores rose from 59.33 to 86.57. Qualitative feedback revealed high participant satisfaction, perceived relevance of training, and suggestions for improvement. This brief pediatric pain education program significantly improved HCPs' knowledge, attitudes, and self-efficacy in a resource-limited setting. The findings highlight the need for ongoing multidisciplinary pain education and refinement of training content for sustained improvements in pediatric pain care.